Pengaruh Kangaroo Mother Care terhadap Self Rfficacy pada Ibu Primipara MOTHER CARE TERHADAP SELF EFFICACY MENYUSUI PADA IBU PRIMIPARA - Pelita Christina L. Tobing; Parida Hanum; Parlaungan Widya Lora Sihombing (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Failure to give exclusive breastfeeding to infants can be caused by factors in the mother's condition such as the mother's confidence or self-efficacy to provide breast milk to her baby. Most primipara mothers have low self-efficacy due to difficulties going through a role transition period and carrying out the demands of their new role as mothers. Kangaroo mother care is a method of skin-to-skin contact between mother and baby (skin-to-skin contact). In kangaroo method care, breast milk can always be available and very easy to obtain, because the baby is near the mother's breast so that the baby can suckle whenever the baby wants it and also increases the mother's bonding so that it can increase the mother's self-efficacy thereby increasing the success of the breastfeeding process. The purpose of this study was to determine the effect of kangaroo mother care on breastfeeding self-efficacy in primiparous mothers at RSU Royal Prima Medan in 2022. This type of research is a quasy experiment using a posttest only control group design. The results of the Independent T-Test test obtained a p-value of 0.000 which is less than 0.05 (0.000 <0.05), so that we can state that Ho is rejected and Ha is accepted. In conclusion, there is the effect of kangaroo mother care on breastfeeding self-efficacy in primiparous mothers at Royal Prima Medan General Hospital in 2022. It is hoped that this research can provide information that kangaroo mother care is very important and useful because it can increase breastfeeding self-efficacy.Key words: Kangaroo Mother Care, ASI, Self Efficacy, Breastfeeding